Let's solve for x.<span><span><span><span>3x</span>y</span>−<span>2x</span></span>=17
</span>Factor out variable x.<span><span>x<span>(<span><span>3y</span>−2</span>)</span></span>=17</span> Divide both sides by 3y-2.<span><span><span>x<span>(<span><span>3y</span>−2</span>)</span></span><span><span>3y</span>−2</span></span>=<span>17<span><span>3y</span>−2</span></span></span><span>x=<span>17<span><span>3y</span>−2</span></span></span>Answer:<span>x=<span>17<span><span>3y</span>−<span>2
</span></span></span></span>
Answer:
Option 3 3 1/8x - 6 3/10
Step-by-step explanation:
(3 1/2x - 4 1/10) - (3/8x + 2 1/5)
Divide it into parts:
(3 1/2x - 3/8x) + (-4 1/10 - 2 1/5)
3 1/2x - 3/8x = 3 4/8x - 3/8x = 3 1/8x
-4 1/10 - 2 1/5 = -4 1/10 - 2 2/10 = -6 3/10
So we get:
2 1/4x - 6 3/10
Answer: The following triangles are congruent.
Answer:
Dont know
Step-by-step explanation:
Sorryyyyyyyyyyyyyyyyyyyyy
Answer:
x = 7, x = -3
Step-by-step explanation:
We can find the zeros by factoring the equation using the zero product property.
x^2-4x-21 = 0
(x-7)(x+3) = 0
<u>x-7 = 0</u>
x = 7
<u>x+3 = 0</u>
x = -3
Zeros are x=7 and x= -3.